2017
DOI: 10.1007/s00300-017-2216-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of phenol by cold-adapted bacteria from Antarctic soils

Abstract: Phenol is an important pollutant widely discharged as a component of hydrocarbon fuels, but its degradation in cold regions is a great challenge due to the harsh environmental conditions. To date, there is little information available concerning the biodegradation of phenol by indigenous Antarctic bacteria. This study addresses the isolation of three phenol-degrading bacterial strains from King George Island, Antarctica. Based on preliminary screening, three isolates (AQ5-05, AQ5-06 and AQ5-07) capable of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 56 publications
7
55
0
Order By: Relevance
“…The temperature optimization experiments carried out here confirmed that both strains were psychrotolerant, growing best at temperatures between 10°C and 15°C. This concurs with the findings of Shukor et al (2009), Margesin et al (2013) and Lee et al (2018).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The temperature optimization experiments carried out here confirmed that both strains were psychrotolerant, growing best at temperatures between 10°C and 15°C. This concurs with the findings of Shukor et al (2009), Margesin et al (2013) and Lee et al (2018).…”
Section: Discussionsupporting
confidence: 94%
“…Studies of non-polluted soils have also revealed psychrophilic or cold-tolerant members of the Arthrobacter genus to be important members of bacterial communities in Antarctic soils (Dsouza et al 2015). Margesin et al (2013) and Lee et al (2018) also reported Arthrobacter spp. strains capable of degrading petroleum hydrocarbons (n-alkanes and phenol) at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of non-polluted soils have also revealed psychrophilic or coldtolerant members of Arthrobacter to be important members of bacterial communities in Antarctic soils (Dsouza et al, 2015). Margesin et al (2013) and Lee et al (2018) also reported that Arthrobacter sp. strains are capable of degrading petroleum hydrocarbons (n-alkanes and phenol) at low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The isolates Arthrobacter sp. strains AQ5-05 and AQ5-06 used in this study were originally isolated from Antarctic soil obtained on King George Island, South Shetland Islands (Lee et al, 2018). The isolates were maintained in glycerol stock at a -80°C at Eco-Remediation Technology Laboratory, Department of Biochemistry, Faculty of Biotechnology and Science Biomolecules, Universiti Putra Malaysia until further use.…”
Section: Sample Collectionmentioning
confidence: 99%
“…In this study, Rhodococcus erythropolis strain AQ5-07, a soil bacterium previously isolated from King George Island (South Shetland Islands, maritime Antarctic; [ 18 ]), was tested for its ability to degrade canola oil and produce biosurfactants, and its growth kinetics were studied and modelled. Canola oil is mostly used in research stations and is use in various cooking techniques, besides it degradation, Rhodococcus erythropolis strain AQ5-07 also could degrade phenol and diesel in addition to heavy metals resistance [ 3 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%